Kesabaran dalam kisah Nabi Yusuf (Studi atas penafsiran M. Quraish Shihab dalam tafsir Al-Misbah) - Ismail, Besid; Kharir, Agus (Department of Ilmu al-Qur'an dan Tafsir, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2021)
Patience is the key of living life; the patient word is often used daily life. Generally, the patience word is used by someone when experiencing the difficult times or in facing problems. Patience is often used as a motivation for someone to be strong to face their problems or difficulties. Qur'an has demonstrated patience in the previous prophet stories, including the story of the Prophet; he is a prophet who has a very high patience level. In the study, the approaching used by researchers is a qualitative with the library research (Library Research) type. This research discusses how the patience according to M. Quraish Shihab is and how is the patience story of Prophet Yusuf. His patience stories according to M. Quraish Shihab is to refrain from all the obstacles that came, while the patience forms in the Prophet Yusuf story, begin with his removed by his brother then, he was found by a group of travelers and sold to the Egyptian. Afterward, Prophet Yusuf patience in resisting the temptation of Aziz wife and he was put in prison because of Aziz wife charges. From those obstacles, the Prophet Yusuf was able to pass it with the great patience. Subsequently, Allah almighty replied with the infinite favors.